INTERNATIONAL STANDARDS OF FAIRNESS IN THAI LEGISLATION ON CRIMINAL PROCEDURE IN JUVENILE CASES STATUTE ON ESTABLISHING JUVENILE AND FAMILY COURT AND THE PROCESS OF CONSIDERING JUVENILE AND FAMILY CASES, 2010, 2016 - Chitov, Alexandre (ASEAN Journal of Legal Studies, 2020)
International human rights law pays significant attention to the procedural rights of young offenders. Legal procedure is conceived as an important element securing the fairness of criminal justice in general and in juvenile cases in particular. One of the requirements of international law is that juvenile offenders have a right to be treated differently. Each juvenile case requires an individualized approach to meet the goals of education. The principle of individualization in juvenile criminal cases comes into tension with the principle of the prohibition of discrimination and the principle of equal application of law (treating like cases alike). This comment illustrates this tension through the examination of procedural fairness in Thai juvenile courts in the light of international law.